Synthesis of cobalt phosphides and their application as anodes for lithium ion batteries - Hoster, Harry E. (2013)
A facile thermal decomposing method has been developed for the fabrication of CoxP nanostructures with controlled size, phase, and shape (e.g., Co2P rod and spheres, CoP hollow and solid particles). An amorphous carbon layer could be introduced by the carbonization of organic surfactants from the precursors. The electrochemical performance of typical CoP and Co2P samples as anode materials has been investigated and the CoP hollow nanoparticle with carbon coating layer depicts good capacity retention and high rate capability (e.g., specific capacity of 630 mA h g–1 at 0.2 C after 100 cycles, and a reversible capacity of 256 mA h g–1 can be achieved at a high current rate of 5 C).